A new genus of hybotid dance fly (Diptera: Hybotidae, Tachydromiinae) from the Eocene Sakhalinian amber - Shamshev, Igor V.; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2025)
The family Hybotidae (Insecta: Diptera, Empidoidea) is recorded for the first time from the bio-inclusions of Sakhalinian amber (Russia). Almost all inclusions studied belong to the subfamily Tachydromiinae. First results suggest that tachydromiines were not uncommon in a palaeo-biotope, where a resin known nowadays as Sakhalinian amber was produced. A new genus and species, Eoplatypalpus sachalinensis gen. et sp. nov., are described and illustrated. In addition, the inclusions of two tachydromiine species of unclear genera (or genus) have been examined but not named. Preliminarily, the palaeo-fauna of Tachydromiinae of Sakhalinian amber is characterised by the presence of only primitive representatives. They show an affinity with the most primitive extant genera of the subfamily (such as Symballophthalmus Becker and Megagrapha Melander) and with the group of extinct genera known from Upper Cretaceous inclusions (Cretoplatypalpus group of genera). The paleontological records of Tachydromiinae are briefly discussed. In addition, it is shown that Symballophthalmus clavilabrosus Hong described from Ypresian Fushun amber of China actually belongs to a different, as of yet uncertain genus. Consequently, fossils of the primitive extant genus Symballophthalmus remain unknown. An identification key to fossil genera of Tachydromiinae (exclusive of Drapetidini) is provided.